The Role of Teachers in Instilling Religious and Moral Values in 5-6 Year Old Children at Mukti Asih Kindergarten - Pipit Ari Kurniawati; Dea, Leli Fertiliana; Ferdian Utama (CV. Creative Tugu Pena, 2024)
This study aims to describe the role of teachers in instilling Religious and moral values in children aged 5-6 years at Mukti Asih Kindergarten. Religious and moral values are very important to be formed from an early age, because at this time children are in the developmental phase. golden age of character development. This study uses a qualitative approach with a case study method. The subjects in this study were two group B teachers and 17 children aged 5-6 years. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results of the study indicate that teachers have a very important role in instilling religious and moral values through habituation activities, role models, storytelling methods, role playing, and providing positive reinforcement. The role of teachers is not only as educators, but also as role models in daily behavior that have a major impact on children's character development. This study contributes to increasing understanding of effective strategies for instilling religious and moral values in early childhood education.